Gontor’s Contribution to National Character Building in Indonesian Islamic Boarding Schools - Edi Bahtiar; Moh In’ami; Zubaidi Wahyono (Universitas Negeri Malang, 2025)
Pesantren has a strategic role in building the national spirit in Indonesia, especially in forming a generation with morals and national insight. Pondok Modern Darussalam Gontor, one of the leading pesantren, implements an education system that integrates Islamic and national values in every aspect of learning. This study aims to analyse how the education system in Gontor shapes the national spirit of santri through curriculum, pesantren culture, and leadership activities. This research uses a qualitative method with a case study approach. Data were collected through observation, in-depth interviews with pesantren caregivers, teachers, and santri, and document analysis related to the curriculum and values taught in Gontor. Data analysis was conducted using triangulation techniques to ensure the validity of the findings. The results show that Gontor instills nationalism through various methods, such as character-based learning, discipline, and independence education, and extracurricular activities that foster a sense of unity and nationalism. The santri leadership system also plays an important role in shaping social responsibility and love for the country. In addition, the integration of Islamic values and nationalism in the curriculum teaches santri about the importance of maintaining the integrity of the nation within the Islamic frame. Thus, education in Gontor can be a model in building a generation that has a strong religious understanding and a high national spirit. Pesantren can contribute to strengthening national unity through value-based education. These findings provide a practical framework for integrating civic and religious education and contribute theoretically to the discourse on nationalism within Islamic educational contexts.